NATURAL BIOLOGICAL NUTRITION - DETERMINATION OF THE PERCENTAGE OF DRY MATTER BY DEHYDRATION OF FOOD ADDITIVES (Scientific journal of the Fergana State University, 2024)
The food we consume includes wet and dry substances. The composition of dry matter includes carbohydrates, fats, proteins, organic acids and minerals. The amount of dry matter in products can be determined by physicochemical, chemical and physical methods. One of the most common methods for determining the amount of dry matter in food is the gravimetric method, which means it can be determined by continuously weighing and removing water from the sample.This article provides information on determining the percentage of dry matter by displacing water from natural dietary supplements.